Ultrasound Detection of Anterior Talofibular Ligament’s Superior Fascicle Ruptures: A Proof-of-Concept Cadaveric Study - Samir Ghandour; Matthias Peiffer; Bedri Karaismailoglu; Soheil Ashkani-Esfahani; Christopher P Miller (Journal of Foot and Ankle Surgery (Asia Pacific))
Objective: To identify ultrasonographic manifestations of isolated superior anterior talofibular ligament (sf-ATFL) injury. Methods: A cadaveric experiment was conducted on a fresh–frozen specimen, during which the superior fascicle was visualized using an open anterior ankle approach, and a stainless-steel clip was applied near its fibular insertion. First, a portable ultrasound examination was performed to reveal normal sonographic features of the sf-ATFL. The ligament was then detached from its fibular insertion, and ultrasound examination was repeated to observe the sonographic signs of sf-ATFL rupture. Results: The sectioned superior fascicle was observed on ultrasound as slack and discontinuous with its fibular insertion. Conclusion: This proof-of-concept study confirms that portable ultrasound can detect a fibular detachment of the sf-ATFL. In clinical practice, the use of portable ultrasound may enable surgeons to diagnose and promptly manage ankle micro-instability.